Problems of Formation and Implementation of the Criminal Law Policy of Counteraction to Terrorism and Armed Aggression (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article is devoted to the study of the problem of formation and implementation of the criminal law policy of counteraction to terrorism and armed aggression. It identifies, describes and explains the existing contradictions between the logics of peace and war in the dimension of competition between the anti-terrorist and anti-war paradigms. It is proved that they lead to misapplication of the law and violations to the principle of equality for citizens before the law. In addition, the ways of eliminating contradictions are proposed by changing approaches to the qualification of terrorist crimes, taking into account the armed conflict as a contextual element in the composition of relevant socially dangerous acts.The final adaptation of the criminal law policy of Ukraine to its implementation in the context of the armed conflict should result in the transition to the qualification of such actions, and in cases where there are grounds for this, under articles providing for criminal liability of Ukrainian citizens for high treason, collaboration, and encroachment on the territorial integrity of Ukraine. As for the combatants, their actions should be qualified not as participation in terrorist organisations, not as terrorist acts, but as a manifestation of military collaborationism, as war crimes. This is required by the logic of war and the paradigm of repulsing the armed aggression carried out by the russian federation with the support of a part of the local population of Ukraine. In the same context, it is necessary to rethink the practice of qualifying a number of other acts committed outside the occupied territory or the territory of active hostilities and currently being legally assessed as terrorist acts.It is emphasised that the prospect of cessation of hostilities on the territory of Ukraine is combined with a number of criminogenic risks of the transition period, including criminal extremism and terrorism. Therefore, by distinguishing the anti-terrorist policy from the policy of legal support for repelling armed aggression, it is necessary to form the readiness of the security sector of our state to respond promptly and adequately to possible terrorist challenges. The latter may be related to the aggressor state's attempts to delegitimise state authorities, provoke international complications, etc.
Keywords: terrorism; terrorist act; aggression; contextual element; armed conflict; war crime; collaboration; treason; criminal law policy; qualification.